Copper‐promoted Synthesis of β‐Selenylated Cyclopentanones via Selenylation and 1,2‐Alkyl Migration Sequences of Alkenyl Cyclobutanols - Kim, Yubin; Kim, Dae Young (Bulletin of the Korean Chemical Society, 2020)
Copper‐promoted selenylation and semipinacol‐type rearrangement of alkenyl alcohols.